2021
DOI: 10.2147/dddt.s326328
|View full text |Cite
|
Sign up to set email alerts
|

The Anticancer Potential of Maslinic Acid and Its Derivatives: A Review

Abstract: Cancer is still an insurmountable problem for humans and critically attacking human health. In recent years, natural products have gained increasing attention in the field of anti-tumor due to their extensive sources and minimal side effects. Maslinic acid (MA), a pentacyclic triterpene acid mainly derived from the olive tree (Olea europaea L.) has been confirmed to possess great anti-cancer effects. This paper reviewed the inhibitory effect of MA and its derivatives on lung cancer, colon cancer, ovarian cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 122 publications
0
6
0
1
Order By: Relevance
“…Salah satu senyawa triterpenoid yang berhasil diisolasi dari akar simpur air yaitu asam 3-epimaslinic (Tor et al, 2015). Asam maslinic diketahui memiliki aktivitas antikanker terhadap sel kanker payudara MCF-7 dengan menghambat proliferasi sel (Yu et al, 2021). Pada fraksi etil asetat senyawa yang diyakini bertanggung jawab terhadap sifat sitotoksik merupakan senyawa yang bersifat polar.…”
Section: Pembahasan Sitotoksisitas Ekstrak Dan Fraksi Terhadap Sel Ka...unclassified
“…Salah satu senyawa triterpenoid yang berhasil diisolasi dari akar simpur air yaitu asam 3-epimaslinic (Tor et al, 2015). Asam maslinic diketahui memiliki aktivitas antikanker terhadap sel kanker payudara MCF-7 dengan menghambat proliferasi sel (Yu et al, 2021). Pada fraksi etil asetat senyawa yang diyakini bertanggung jawab terhadap sifat sitotoksik merupakan senyawa yang bersifat polar.…”
Section: Pembahasan Sitotoksisitas Ekstrak Dan Fraksi Terhadap Sel Ka...unclassified
“…Natural pentacyclic triterpenic acids of the ursane and oleanane series, including oleanolic, ursolic, maslinic, and corosolic acids, are widely found in the plant kingdom ( Figure 1 ) [ 1 , 2 ]. These secondary plant metabolites exhibit a diverse range of biological properties, with their cytotoxic activity and capacity to initiate the mitochondrial pathway of apoptosis in various tumor cells being of particular interest [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. For instance, oleanolic acid induces apoptosis in non-small lung cancer cell lines, even in the presence of anti-apoptotic Bcl-2 proteins, and reduces metastasis in vivo in the B16F10 melanoma model [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous preclinical studies have confirmed the therapeutic potential of maslinic acid and its semi-synthetic derivatives in various tumor types, demonstrating this triterpenoid’s ability to inhibit proliferation, stimulate apoptosis, and obstruct cancer cell angiogenesis [ 8 , 9 ]. Corosolic acid effectively triggers apoptosis in HeLa cervical adenocarcinoma and human prostate cancer (PC-3 and DU145 lines) while exhibiting low toxicity to normal cells and tissues [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the relevant components present in the olive oil extract is maslinic acid (MA), a pentacyclic triterpene present in skins and seeds of olive fruits, that is extracted in the pomace oil ( Mokhtari et al, 2015 ). MA has demonstrated health benefits derived from its antioxidant, anti-inflammatory, antimicrobial, hepato-protective and anticancer properties ( Sánchez-Quesada et al, 2013 ; Lozano-Mena et al, 2014 ; Jing et al, 2021 ), and this molecule could influence cell physiology in a dose-dependent manner ( Yu et al, 2021 ). However, to our best knowledge, it potential effect for the stimulation of human skin keratinocyte cell cultures growth has not been described to the date.…”
Section: Introductionmentioning
confidence: 99%